2018
DOI: 10.1111/anae.14273
|View full text |Cite
|
Sign up to set email alerts
|

Topical application of corticosteroids to tracheal tubes to prevent postoperative sore throat in adults undergoing tracheal intubation: a systematic review and meta‐analysis

Abstract: Postoperative sore throat negatively affects patient satisfaction and recovery. Numerous randomised trials have tested the efficacy of corticosteroids applied to tracheal tubes to prevent postoperative sore throat. We searched PubMed, EMBASE, the Cochrane Central Register of Controlled Trials, Wanfang Database, and the China Academic Journal Network Publishing Database from inception to 7 December 2017. We included randomised controlled trials that assessed the efficacy and safety of corticosteroids applied to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
35
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 59 publications
(86 reference statements)
2
35
0
1
Order By: Relevance
“…Previous studies have suggested that topical application of ketamine and corticosteroids help to prevent postoperative sore throat. 17,47 Our study suggests that intravenous dexamethasone is superior to topical ketamine, while topical corticosteroids and most analgesic agents combined with intravenous dexamethasone are no better than intravenous dexamethasone alone. Nevertheless, most of these comparisons were performed in single, small-sized trials and we believe that additional studies of this nature are warranted.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Previous studies have suggested that topical application of ketamine and corticosteroids help to prevent postoperative sore throat. 17,47 Our study suggests that intravenous dexamethasone is superior to topical ketamine, while topical corticosteroids and most analgesic agents combined with intravenous dexamethasone are no better than intravenous dexamethasone alone. Nevertheless, most of these comparisons were performed in single, small-sized trials and we believe that additional studies of this nature are warranted.…”
Section: Discussionmentioning
confidence: 80%
“…The presumed etiology underlying postoperative sore throat is mucosal inflammation around the tracheal tube cuff. 12 Previous studies suggest that topical and intravenous anti-inflammatory agents prevent postoperative sore throat in surgical patients, [16][17][18]45 thus supporting this explanation. Furthermore, intravenous corticosteroids administered to critical care patients prior to elective extubation decrease laryngeal edema and reduce post-extubation airway complications.…”
Section: Discussionmentioning
confidence: 91%
“…We compared ketamine with numerous comparators that have been proven to prevent postoperative sore throat, [15][16][17][18][19][20][21] including topical lidocaine and corticosteroids as well as intravenous dexamethasone. However, comparisons of these treatments were performed in a limited number of small-sized studies, and the non-superiority Ketamine administration is associated with unwanted outcomes such as psychomimetic effects and blood pressure rise.…”
Section: Discussionmentioning
confidence: 99%
“…These same authors have recently published several other systematic reviews and meta-analyses summarizing the literature describing other effective treatments of POST, including intravenous dexamethasone (pooled risk ratio [RR], 0.62; 95% confidence interval [CI], 0.51 to 0.75), 7 topical benzydamine (RR, 0.31; 95% CI, 0.20 to 0.47), 8 and topical corticosteroids (RR, 0.39; 95% CI, 0.32 to 0.49). 9 Multiple other treatments have been studied and found to be effective at reducing the incidence and severity of sore throat including lidocaine (either intra-cuff 10 or intravenously administered), 11 ketamine, 12 with even the choice of volatile anesthetic playing a role (desflurane is associated with a higher incidence of POST than sevoflurane). 13 The current systematic review and meta-analysis by Kuriyama et al provides an opportunity to consolidate the literature supporting topical magnesium as a highly effective treatment for POST.…”
mentioning
confidence: 99%
“…7 la benzydamine topique (RR, 0,31; IC 95 %, 0,20 à 0,47), 8 et les corticostéroïdes topiques (RR, 0,39; IC 95 %, 0,32 à 0,49). 9 Plusieurs autres traitements ont été étudiés et leur efficacité a été démontrée pour réduire l'incidence et la gravité des maux de gorge, comme par exemple la lidocaïne (à l'intérieur du ballonnet 10 ou par administration intraveineuse), 11 la kétamine, 12 le choix d'agent anesthésique volatile jouant lui-même un rôle (par exemple, le desflurane est associé à une incidence plus élevée de maux de gorge postopératoires que le sévoflurane). 13 La revue systématique et la méta-analyse de Kuriyama et coll.…”
unclassified